Tsunami And Storm Surge Modeling In Bay Of Bengal - Cham, Kah Loon (2007)
Destruction due to 26 December 2004 Andaman tsunami has become a major concern to the communities around the world. Several efforts have been undertaken to minimize the potential impacts of future tsunamis. In this thesis, a theoretical investigation of tsunami propagation properties and characteristics, with particular reference to the 26 December 2004 Andaman tsunami will be presented to highlight the potential risks and vulnerability of the countries around the Bay of Bengal, with the assistance of a tsunami simulation model TUNA-M2. This thesis will also discuss ocean circulation and storm surge modeling in the Bay of Bengal. TUNA-M2 is then modified to TUNA-SU by incorporating four additional terms: wind forcing, sea level pressure (SLP) gradient, Carialis force and horizontal eddy viscosity. For ocean circulation study, TUNA-SU incorporates long-term averaged winds of the southwest and northeast monsoon to simulate the ocean circulations in the Bay of Bengal. The simulated current circulations by means of TUNA-SU are compared to the observed current patterns. For storm surge study, TUNA-SU incorporates a parametric wind field model, the Modified Rankine Vortex model to simulate the surge levels along the affected coastal areas in Myanmar for the event of 1992 Sandoway cyclone. The simulated surge levels are compared to the reported surge heights. It is hoped that this thesis will contribute towards further research on tsunami, storm surge and ocean circulation modeling in the future.